Legal problems of e-commerce taxation regulation - Anatolyevna Kirillova, Albert Gumarovich Yakupov, Timur Giorgievich Okriashvili, Albert Valentinovich Pavlyuk, Elena (Opción, 2019)
This article discusses the legal problems of taxation regulation e-Commerce via collection and study of individual facts; generalization; methods of scientific abstraction; methods of regularity cognition. As a result of the analysis, it is proved that a computer server owned by a foreign enterprise and located in another state can be recognized as a permanent establishment for the purposes of taxation of income of a foreign enterprise from activities in that state. The article concluded that it is necessary to form a special definition of e-Commerce, which will be used exclusively for tax purposes.